2011
DOI: 10.1038/emboj.2011.365
|View full text |Cite
|
Sign up to set email alerts
|

Optic atrophy 1 is an A-kinase anchoring protein on lipid droplets that mediates adrenergic control of lipolysis

Abstract: Adrenergic stimulation of adipocytes yields a cAMP signal that activates protein kinase A (PKA). PKA phosphorylates perilipin, a protein localized on the surface of lipid droplets that serves as a gatekeeper to regulate access of lipases converting stored triglycerides to free fatty acids and glycerol in a phosphorylation-dependent manner. Here, we report a new function for optic atrophy 1 (OPA1), a protein known to regulate mitochondrial dynamics, as a dual-specificity A-kinase anchoring protein associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 69 publications
(110 reference statements)
8
116
1
Order By: Relevance
“…The fact that Mfn1 does not interact with PLIN1 and that mutation of the GTPase activity of Mfn2 abolishes this binding further testifies for the specificity and relevance of the Mfn2‐PLIN1 interaction. It has been previously proposed that OPA1 could assemble a supramolecular complex containing PKA and perilipin and would be responsible for LD–mitochondria interactions (Pidoux et al , 2011). OPA1, however, generally localizes to the inner mitochondrial membrane, which might force the need for molecular adaptors in order to interact with proteins residing outside of the outer mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that Mfn1 does not interact with PLIN1 and that mutation of the GTPase activity of Mfn2 abolishes this binding further testifies for the specificity and relevance of the Mfn2‐PLIN1 interaction. It has been previously proposed that OPA1 could assemble a supramolecular complex containing PKA and perilipin and would be responsible for LD–mitochondria interactions (Pidoux et al , 2011). OPA1, however, generally localizes to the inner mitochondrial membrane, which might force the need for molecular adaptors in order to interact with proteins residing outside of the outer mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, protein kinase A anchoring proteins are able to bind to the regulatory subunit of PKA and lead to subcellular compartmentalization of cAMP-PKA signaling (70,71). In adipocytes, it has been reported that optic atrophy 1, a regulator of mitochondrial dynamics, acts as a protein kinase A anchoring protein in lipid droplets and facilitates lipolysis upon stimulation (72). Thus, the regulatory mechanisms of PKA activity and lipolysis by subcellular distribution of RI␣ and RII␤ would be important to pursue in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…For colocalization between BACE1 and synaptophysin, line profiles from the two fluorescent channels were analyzed using the ImageJ red-green-blue (RGB) Profiler plug-in (41). Briefly, neurons were transfected for BACE1-mRFP together with eGFP or RTN3-eGFP, and the fixed neurons on the coverslip were stained with an antibody against synaptophysin.…”
Section: Methodsmentioning
confidence: 99%